OFR-77-80 Development Of A Deep-Penetrating Borehole Geophysical Technique For Predicting Hazards Ahead Of Coal Mining - Sidney A. Suhler (The National Institute for Occupational Safety and Health (NIOSH), 1978)
A field operable, breadboard model, borehole radar was developed for the detection of hazardous geological anomalies in and above a coal seam in advance of mining. A four-inch diameter downhole probe was fabricated and tested in several environments. The radar transmitter was also employed in a cross-hole or through transmission mode to determine natural geotechnical and man-made conditions between boreholes. Sensitivity to underground conditions in both modes of operation were indicated.